A prospective in silico analysis of interdisciplinary and interobserver spatial variability in post-operative target delineation of high-risk oral cavity cancers: Does physician specialty matter?. (August 2018) - Ng, Sweet Ping; Dyer, Brandon A.; Kalpathy-Cramer, Jayashree; Mohamed, Abdallah Sherif Radwan; Awan, Musaddiq J.; Gunn, G. Brandon; Phan, Jack; Zafereo, Mark; Debnam, J. Matthew; Lewis, Carol M.; Colen, Rivka R.; Kupferman, Michael E.; et al.
Abstract: Background: The aim of this study was to determine the interdisciplinary agreement in identifying the post-operative tumor bed. Methods: Three radiation oncologists (ROs), four surgeons, and three radiologists segmented post-operative tumor and nodal beds for three patients with oral cavity cancer. Specialty cohort composite contours were created by STAPLE algorithm implementation results for interspecialty comparison. Dice similarity coefficient and Hausdorff distance were utilized to compare spatial differentials between specialties. Results: There were significant differences between disciplines in target delineation. There was unacceptable variation in Dice similarity coefficient for each observer and discipline when compared to the STAPLE contours. Within surgery and radiology disciplines, there was good consistency in volumes. ROs and radiologists have similar Dice similarity coefficient scores compared to surgeons. Conclusion: There were significant interdisciplinary differences in perceptions of tissue-at-risk. Better communication and explicit description of at-risk areas between disciplines is required to ensure high-risk areas are adequately targeted.